A Usable Collection: Essays in Honour of Jaap Kloosterman on Collecting Social History - Lucassen, Jan; Sanders, Huub; Blok, Aad (Amsterdam University Press, 2014)
Established in 1935, the International Institute of Social History (IISH) is one of the world's leading research institutes focused on social history and holds one of the richest collections in the field. This volume brings together thirty-five essays in honor of the IISH's longtime director Jaap Kloosterman, who built the institute into a world leader in the field.